1998
DOI: 10.1097/00000539-199802000-00031
|View full text |Cite
|
Sign up to set email alerts
|

The Analgesic Effect of Fentanyl, Morphine, Meperidine, and Lidocaine in the Peripheral Veins

Abstract: Propofol, a commonly used anesthetic, often causes pain on injection. Given as venous retention pretreatments 1 min before propofol, meperidine and lidocaine were found to significantly reduce the propofol injection pain, whereas fentanyl and morphine only slightly reduced the propofol injection pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 20 publications
2
30
0
Order By: Relevance
“…11 In our study, the overall incidence of pain during i.v. injection of propofol in the lidocaine group was 8% and it was similar to the results of Pang and colleagues 12 who reported it to be 11%. But, in some other studies higher incidences, such as 18% 13 or 42%, 11 have been reported.…”
Section: Discussionsupporting
confidence: 88%
“…11 In our study, the overall incidence of pain during i.v. injection of propofol in the lidocaine group was 8% and it was similar to the results of Pang and colleagues 12 who reported it to be 11%. But, in some other studies higher incidences, such as 18% 13 or 42%, 11 have been reported.…”
Section: Discussionsupporting
confidence: 88%
“…Delayed pain has a latency of between 10 -20 secs. (6) Up to now, the mechanism of pain due to propofol injection has been unclear. Propofol belong to the group of phenols and can directly irritate the skin, mucous membrane and venous intima and could immediately stimulate nociceptors and free nerve endings.…”
Section: Resultsmentioning
confidence: 99%
“…Pang et al showed that tramadol has local anaesthetics effects. 6 Hamid Zahedi et al evaluated that tramadol and ondansetron significantly reduced the incidence and severity of propofol injection pain. 19 In this study, we observed a high incidence of pain in 85% of patients in saline group during propofol injection which was decreased to 12.5% and 20% after tramadol and ondansetron pre-treatment respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Several methods for prevention of pain have been tried with varying degrees of success like addition of lignocaine, [2,3,9] cooling [10,11] or warming [12] of the drug, diluting propofol solution [5,13], pretreatment with ondansetron [14], metoclopramide [15], opioids [16], thiopentone [17], paracetamol [18], dexamethasone [19] and dexmedetomidine [20]. Analgesic effect of lignocaine may occur because of a local anesthetic effect or an inhibitory effect on the enzymatic cascade which leads to release of kinins [3].…”
Section: Discussionmentioning
confidence: 99%